A theory of superconductivity in cuprates - Plakida, N.M. (Condensed Matter Physics, 2005)
A microscopic theory of superconducting pairing mediated by antiferromagnetic (AFM) exchange and spin-fluctuations is developed within the effective p − d Hubbard model for the CuO₂ plane. It is proved that retardation effects for AFM exchange interaction are unimportant and result in pairing of all electrons in the conduction band and high Tc proportional to the Fermi energy. The spin-fluctuations caused by the kinematic interaction give an additional contribution to the d-wave pairing. Tc dependence on the hole concentration and lattice constants (or pressure) is studied. Small oxygen isotope shift of Tc is explained. The data are compared with the results for the t − J model. Розроблено мікроскопічну теорію надпровідного спарювання через антиферомагнітний (АФМ) обмін та спін-флуктуації в рамках ефективної p − d моделі Хаббарда для площини CuO₂. Доведено, що запізнюючі ефекти для АФМ обмінної взаємодії є неважливими і приводять до спарювання всіх електронів у зоні провідності та високої Tc, пропорційної до енергії Фермі. Спін-флуктуації, спричинені кінематичною взаємодією, дають додатковий внесок у спарювання d-типу. Досліджується залежність Tc від концентрації дірок та сталої гратки (чи тиску). Пояснено малий зсув Tc від ізотопів кисню. Отримані дані порівнюються з результатами для t − J моделі.